Scaling-up and future sustainability of a national reproductive genetic carrier screening program - Fehlberg, Z; Best, S; Long, JC; Theodorou, T; Pope, C; Hibbert, P; Williams, S; Freeman, L; Righetti, S; Archibald, AD; Braithwaite, J (Springer Nature, 2023)
An understanding of factors influencing implementation is essential to realise the benefits of population-based reproductive genetic carrier screening programs. The aim of this study was to synthesise data collected during the Australian Reproductive Genetic Carrier Screening Project (Mackenzie’s Mission) to track how priorities shifted over time and identify important factors during scaling-up and for sustainment. We used a multi-method qualitative approach to integrate longitudinal project data collected from 10 project committees with 16 semi-structured interviews conducted with study team members. Both datasets were analysed using the Consolidated Framework for Implementation Research (CFIR) to identify constructs of interest within early, mid-point, and future implementation phases. Several CFIR constructs were present across implementation. The complexity of implementation presented challenges that were overcome through a quality-designed and packaged product, formal and informal networks and communication, and access to knowledge and information. Addressing the diverse consumer needs through resources and increasing community and non-genetic speciality engagement remained a priority throughout and for future sustainment. Going forward, further addressing program complexities and securing funding were emphasised. By applying an implementation framework, findings from this study may be useful for future effort towards building and/or sustaining reproductive genetic carrier screening programs.